Peran Endomikoriza dan Tingkat Ketersediaan Air pada Tanah Vertisol terhadap Peningkatan Serapan Fosfor dan Hasil Paprika - Onesimus Ke Lele (Fakultas Pertanian, Universitas Timor, 2023)
Endomycorrhizae is known as a potential biological fertilizer for dry land because of its ability to provide nutrients for plants in sub-optimal conditions. Several studies have suggested that mycorrhizae can increase nutrient uptake, especially phosphorus, potassium, and can also increase the tolerance of plants growing in nutrient and water crisis soil conditions. This research was conducted to examine the influence of endomycorrhizae on different water availability conditions in vertisol soils cultivated by paprika. In this study, statistically it has not proven the efficacy of endomycorrhizae in increasing available P nutrients, P uptake and yields of paprika on vertisol soils with different levels of water availability. The treatment of 60% water availability was not enough to make paprika plants gripped so that the presence of endomycorrhizae did not have an effect on the results of several observed variables. However, at 80% groundwater availability, the field capacity increased the available P, the number of flower buds and the number of paprika flowers formed. Based on this research experience, it is recommended that before endomycorrhizal application, it is necessary to sterilize the soil to be used as a medium first. In addition, the use of endomycorrhizae as a treatment, it is better to isolate pure spores that have been identified to the genus or even certain species, not in the form of soil propagules.